Perempuan di Sekitar Markas Besar Komando Djawa Kalibawang, Yogyakarta, 1948-1949 - Ahmad Athoillah (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
This research studies women's history at MBKD post during the Indonesia revolution period in 1948-1949 in Kalibawang, Yogyakarta. The history of the MBKD post has always been linked to the roles of men such as A.H. Nasution. Meanwhile, the study on women were mostly focused on their role in the public kitchen. There was no study which explored the women’s other life experience during this period of time in this particular place. Hence, this article aims to expose and explain the daily forms of women's experiences when the region was used as an MBKD post. This research uses historical method by gathering oral sources from the witnesses and perpetrators. Recalling daily experiences of women around the MBKD at the time of the second Dutch military aggression was gathered through deep interview with the witnesses. The findings of this study include insight on the forms and types of activities conducted by women during certain designated time, as well as social settings. The research also reveals the everyday world, the roots of social life, and the daily hopes of women at Kalibawang. There is also a new conception that arise among women about the diffusion of social life over the region. All of this occurred when Kalibawang was used as MBKD post in 1948-1949. Conclusively, this study may serve as inspiration on how to explore women’s history that goes beyond the issues of their status and role.